Efektivitas Guru dalam Mengembangkan Pembelajaran Konstruktif dalam Pendidikan Kewarganegaraan - Dewi, Dinie Anggraeni; Nuraeni, Nani (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2017)
The background of this study is the importance of teachers’ pedagogical competence in developing their professional duties by developing the learning activities as many as it could to achieve the learning outcomes from the learners. This is only possible if the teachers involve the thinking construct of learners in the learning process effectively by considering the available time aspect to gain optimal achievements in learning outcomes. This paper is the result of an in-depth research of the civic teachers who effectively develop constructive learning and show positive results in the learning quality of their students in the primary education level of junior high school. In order to obtain the meaning of the research objective, the researcher employs an integrated qualitative and quantitative approaches. The result of the study found that teachers’ effectiveness in developing constructive learning is showed by an attempt to create a productive learning atmosphere in the process of learning and to in-volve various learning interaction patterns to explore learners’ thinking skill in a high level. Keywords: teachers’ effectiveness, constructive learning, quality of learning outcomes ABSTRAK Penelitian ini dilatarbelakangi dengan pentingnya kompetensi pedagogik guru dalam mengembangkan tugas profesinya yakni mengembangkan pembelajaran untuk sebesar-besarnya mencapai hasil belajar peserta didik. Hal ini hanya mungkin dapat dicapai apabila guru efektif melibatkan konstruk berfikir peserta didik dalam proses pembelajarannya, yakni mempertimbangkan aspek waktu yang tersedia untuk memperoleh capaian hasil belajar optimal. Tulisan ini merupakan hasil penelitian mendalam terhadap guru Pendidikan Pancasila dan Kewarganegaraan yang efektif mengembangkan pembelajaran konstruktif dan menunjukkan hasil positif terhadap kualitas belajar peserta didiknya pada jenjang pendidikan dasar Sekolah Menengah Pertama. Untuk memperoleh makna tujuan penelitian, digunakan pendekatan kualitatif dan kuantitatif secara terpadu. Hasil penelitian efektifitas guru dalam mengembangkan pembelajaran konstruktif ditunjukkan dengan upayanya untuk menciptakan suasana yang produktif dalam proses belajar dan melibatkan pola interaksi pembelajaran variatif untuk menggali keterampilan berfikir peserta didik pada tingkat tinggi. Kata kunci: efektifitas guru, pembelajaran konstruktif, kualitas hasil belajar